2019
DOI: 10.2147/ott.s191016
|View full text |Cite
|
Sign up to set email alerts
|

<p>CHFR promotes the migration of human gastric cancer cells by inducing epithelial-to-mesenchymal transition in a HDAC1-dependent manner</p>

Abstract: BackgroundPrevious studies have illustrated that checkpoint with forkhead-associated and ring finger domains (CHFR) was frequently silenced in several cancer types due to promoter hypermethylation and functions as a tumor suppressor gene. However, the data from the public dataset reveal that CHFR is highly expressed in human gastric cancer specimens, and the biological function of CHFR in gastric cancer is still not well understood.Materials and methodsThe clinical association between CHFR expression and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…On the other hand, at the 24‐hr time‐point, many genes were consistently upregulated in at least four cell lines. Table 1 displays the list of these genes, the information on family, molecular function ligands (lipid transport‐associated), subcellular localization, and cancer‐associated expression patterns of their encoded proteins are also provided (Carrara et al., 2018; Chen et al., 2020; Esau et al., 2016; Gordon et al., 2019; D. Jiang et al., 2020; Koochekpour et al., 2007; Swanton et al., 2007; Thorsen et al., 2011; Verma et al., 2020; Yang, He, et al., 2019; M. Zhang, Xiang, et al., 2020; Zheng et al., 2018). It was observed that STARD4, OSBPL9 LDLR, and SCARB1 genes were significantly upregulated in all the LPDS‐treated (24 hr) cell lines, whereas CERT1, OSBPL5, OSBPL1A, APOLD1, APOL5, CTEP, PSAP, CFHR4, APOO, and SLC27A6 were upregulated in at least four of the five cell lines (Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, at the 24‐hr time‐point, many genes were consistently upregulated in at least four cell lines. Table 1 displays the list of these genes, the information on family, molecular function ligands (lipid transport‐associated), subcellular localization, and cancer‐associated expression patterns of their encoded proteins are also provided (Carrara et al., 2018; Chen et al., 2020; Esau et al., 2016; Gordon et al., 2019; D. Jiang et al., 2020; Koochekpour et al., 2007; Swanton et al., 2007; Thorsen et al., 2011; Verma et al., 2020; Yang, He, et al., 2019; M. Zhang, Xiang, et al., 2020; Zheng et al., 2018). It was observed that STARD4, OSBPL9 LDLR, and SCARB1 genes were significantly upregulated in all the LPDS‐treated (24 hr) cell lines, whereas CERT1, OSBPL5, OSBPL1A, APOLD1, APOL5, CTEP, PSAP, CFHR4, APOO, and SLC27A6 were upregulated in at least four of the five cell lines (Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 displays the list of these genes, the information on family, molecular function ligands (lipid transport-associated), subcellular localization, and cancer-associated expression patterns of their encoded proteins are also provided (Carrara et al, 2018;Chen et al, 2020;Esau et al, 2016;Gordon et al, 2019;D. Jiang et al, 2020;Koochekpour et al, 2007;Swanton et al, 2007;Thorsen et al, 2011;Verma et al, 2020;Yang, He, et al, 2019;M. Zhang, Xiang, et al, 2020;Zheng et al, 2018).…”
mentioning
confidence: 99%
“…For example, HDAC1 has been demonstrated to be tumor promoter in a range of malignancies, covering gastrointestinal tumors such as colorectal cancer [ 18 ], and gastric cancer [ 19 ], as well as HCC [ 20 ] and ovarian cancer [ 21 ]. Inhibition of this HDAC has recently been corroborated to prevent the progression of gastric cancer [ 22 ] and esophageal carcinoma [ 23 ]. The major results from the present study revealed that HDAC1 was highly expressed in CC clinical samples and cells, whereas shRNA-induced silencing of HDAC1 contributed to prevention against CC progression, supported by the restrained proliferative, migratory and invasive capabilities of CC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the CHFR gene is significantly silenced or mutated by promoter methylation in many cancer types including nonsmall cell lung cancer (Mizuno et al, 2002) and esophageal cancer (Shibata et al, 2002). Yang et al (2019) found that CHFR promoted the invasion of gastric cancer cells by inducing epithelial to mesenchymal transformation in a HDAC1dependent manner. Coronin-6, a gene product of CORO6, is a member of the coronin family and has been shown to play a role in cell movement, vesicle transport, and cell division (Roadcap et al, 2008).…”
Section: Discussionmentioning
confidence: 99%